1990
DOI: 10.1139/p90-010
|View full text |Cite
|
Sign up to set email alerts
|

Some interesting features of charged particles produced in high-energy hadron–emulsion collisions

Abstract: The emission characteristics of secondary charged particles produced in 400 GeV proton-emulsion interactions were compared with those obtained at other energies. The results revealed that the angular distribution of grey particles does not depend on the nature and energy of the projectile. The dependence of the average multiplicity of the grey, black, shower, and heavily ionizing tracks on the mass of the target nucleus (A) and the nature and energy of the projectiles are also examined. The ratio of the valanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…It is interesting to note that the values of C K in 4.5 A GeV/c 12 C-nucleus reactions and 28 Si-nucleus collisions are almost consistent with constant with the statistical limits. It may be further noted in the Table-1 that, the value of this parameter is observed to increase with increasing value of k. On comparing the findings of the present work with those obtained in 50 GeV and 400 GeV hadron-nucleus collisions [4], it may be observed that the value of C K are very similar in both type of interactions. The k th root of the central moment, µ K of the multiplicity distribution is also studied in 4.5 A GeV/c 28 Si-nucleus collisions.…”
Section: The Characteristics Of Secondary Charged Particles Produced supporting
confidence: 73%
See 1 more Smart Citation
“…It is interesting to note that the values of C K in 4.5 A GeV/c 12 C-nucleus reactions and 28 Si-nucleus collisions are almost consistent with constant with the statistical limits. It may be further noted in the Table-1 that, the value of this parameter is observed to increase with increasing value of k. On comparing the findings of the present work with those obtained in 50 GeV and 400 GeV hadron-nucleus collisions [4], it may be observed that the value of C K are very similar in both type of interactions. The k th root of the central moment, µ K of the multiplicity distribution is also studied in 4.5 A GeV/c 28 Si-nucleus collisions.…”
Section: The Characteristics Of Secondary Charged Particles Produced supporting
confidence: 73%
“…The normalized moments of the multiplicity distributions of relativistic charged particles produced in high energy hadron-nucleus collisions has been investigated by several workers in the energy range ~ (50-400) GeV [4]. However, a little attention has been paid to study the normalized moments of the multiplicity distributions of relativistic charged particles produced in nucleus-nucleus interactions [3,6].…”
Section: The Characteristics Of Secondary Charged Particles Produced mentioning
confidence: 99%